Analysis of a Frictionless Electro Viscoelastic Contact Problem with Signorini Conditions - Boulaouad, A.; Ourahmoun, A.; Serrar, T. (Engineering, Technology & Applied Science Research, 2022)
This study considered a mathematical model to describe the process of a quasi-static contact between a piezoelectric body and an electrically conductive foundation. The behavior of the material was modeled with a nonlinear electro-viscoelastic constitutive law, the contact was frictionless, and the result was described with the Signorini condition. A variational formulation was derived for the problem, proving the existence and uniqueness of a weak solution of the model. The proof was based on arguments for nonlinear equations with maximal monotone operators.